Layanan Transportasi dalam Pengembangan Pariwisata di Kabuapten Kerinci - Baddal Hayat Al Abror; Okto Risdianto Manullang (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
Indonesia is one of the best tourist destination countries in the world.  It can be concluded fromthe availability of tourism transportation services in Indonesia. Sungai Penuh as a promoted city of Regional Activity Center (PKWp) has not served as the brand of Kerinci Regency for tourism in Jambi Province. It is caused by the lack of route services of public transportation for tourism in Kerinci Regency.  The purpose of this study is to determine the form of transportation services in the tourism development of Kerinci Regency. The analytical method used in this study was quantitative descriptive method by utilizing questionnaire data, observation interviews and documents to identify tourist characteristics, tourism activities and transportation infrastructure. The data processing was using Arcgis Software on Route Analysis, in order to find out the travel time, travel distance, costs incurred and types of tourist movements. The results of this study shows that there are two types of movements, which are the type of tour movement determined  by the closest distance between attractions and the type of trip destination movement determined  by the length of time needed  to reach a tourist attraction.  The result will be displayed in the form of Kerinci Regency tourism map. It is expected that with the availability of tourism transportation services in Kerinci regency, tourists could travel easily, safely and comfortably, which is expected to attract the number of tourists and increase the economic activities in Sungai Penuh.